Two new species of the genus Phaea Newman, 1840 (Coleoptera: Cerambycidae) from Mexico - Toledo-Hernández, Víctor Hugo; Martínez-Hernández, José G.; Bezark, Larry (Zootaxa, 2016)
Two new species of the genus Phaea Newman are described from Mexico. Phaea chemsaki sp. nov. from Chiapas, and P. parallela sp. nov. from Morelos. The descriptions are supplemented with photographs.